Novyi podkhod k ustraneniyu funktsional'nogo blokirovaniya dvigatel'nykh segmentov v razlichnykh otdelakh pozvonochnika u yunykh sportsmenov - Pismenski, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this study was to reveal the frequency of functional blocking in various parts of young athletes'spinal column and elaborate a wide available complex of exercises helping to eliminate that blocking. 104 young athletes aged from 8 to 18 (males) specialising in rowing, swimming and football acted as subjects. The author offers seven exercises to eliminate the functional blocking of some parts in young athletes spinal column, basing on the theory of the cranio-sacral respiratory mechanism and its disorders' classification. The performed experiment had roved the symmetrical and statistically significant increase of the subjects foots'arch .